Common Carotid Artery Intima-Media Thickness Reflects the Cumulative Burden of Atherosclerosis and Predicted Well by Total-C/HDL-C Ratio in Type-II Diabetic Patients- A Case Control Study Based from Kolkata, India - Sau, Tanmay Jyoti; Dey, Sandip Kumar; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2013)
Background: Diabetes Mellitus (DM) is frequently associated with the development of premature atherosclerotic vascular disease and is the major cause of morbidity and mortality. Approximately 80% of all deaths and more than 75% of all hospitalizations are due to CAD. Individuals with DM are usually associated with accelerated atherosclerosis. Common Carotid artery intima-media thickness (CCAIMT) is now also considered as a surrogate marker of atherosclerosis. Materials and Methods: This case-control study was conducted from Jan, 2011 to June, 2012 among Type-II diabetes, aged between 30-80yrs. Patients with Type-I diabetes, aged <30yrs or >80yrs and other secondary causes of diabetes, hypertensive, smokers and patients under therapy with lipid lowering drugs were excluded from this study. The biochemical tests were done in the department of Biochemistry, Nilratan Sarkar Medical College and Hospital, using standardized reagent kits. CCAIMT was measured by high resolution imaging using 10MHz transducer in the department of Radiodiagnosis, Nilratan Sarkar Medical College and Hospital. Results: The results of our study indicate that dyslipidemic diabetic patients had significantly higher blood glucose at any phase along with glycated haemoglobin compared to controls. The lipid variables were also significantly higher in the diabetes patients with dyslipidemia compared to controls except HDL levels were significantly higher in control. CCAIMT was higher in the dyslipidemic group (1.71 ± 0.57mm) compared to the non-dyslipidemic group (0.77 ± 0.10) which was statistically significant (p value <0.001). Conclusion: CCAIMT reflects the cumulative burden of atherosclerosis and is highly correlated and predicted well by Total-C/HDL-C ratio in Type-II diabetic patients. So it is advised that a direct examination of the vessel wall is extremely essential for early detection of the affected individuals so that the cost burden in Intensive coronary care unit can be minimized and also the individual can be advised to control the extensive dyslipidemia through dietary restrictions and exercise. DOI: http://dx.doi.org/10.3126/ajms.v5i1.8450 Asian Journal of Medical Science Vol.5(1) 2014 pp.9-14